Implementasi Aplikasi Jamsostek Mobile Dalam Pengajuan Klaim Jaminan Hari Tua Pada BPJS Ketenagakerjaan Cabang Kota Bogor - Afandi, Much; Muktiadji, Nusa; Rosita, Siti Ita; Rosa, Edy Safni (Program Vokasi dan LPPM IBI Kesatuan, 2025)
Implementation of Worker Insurance Application _______161 Submitted OCTOBER 2024 Accepted JUNE 2025 JABKES Jurnal Aplikasi Bisnis Kesatuan Vol. 5 No. 2, 2025 page. 161 - 178 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v5i2.41955 Old-age security provides guarantees to workers in the form of cash benefits paid periodically or in a lump sum to workers who are participants of the Old Age Security (JHT) program in accordance with the prevailing regulations. The system and procedures for claiming Old Age Security require participating workers to go through several stages of the claim process. Claims can be made either by visiting the branch office in person or via online media. The purpose of this final project discussion is to understand the claim system and procedures conducted directly or through the Jamsostek Mobile (JMO) application for workers who have become participants of the Old Age Security at BPJS Ketenagakerjaan, as well as to provide an overview of the calculation of the old-age security balance. The results of the discussion indicate that the system and procedures for claiming old-age security funds implemented by BPJS Ketenagakerjaan Branch Bogor City comply with the regulations of the Social Security Administering Body for Employment. The Jamsostek Mobile (JMO) application is used as a medium and one of the methods for claiming old-age security funds online. However, there are still application development issues that hinder participants who wish to claim their old-age security. As a result, participants must visit the nearest branch office for further processing. Regarding the calculation of the Old Age Security balance, the benefits are greater if claimed at an older age rather than at a younger age. This aligns with the purpose of the Old Age Security, which is meant for the participant's old age. The income from the development interest of the old-age security balance makes the benefits more substantial if claimed in old age, as the development interest will increase the participant's balance even if the participant no longer pays contributions. Keywords : Old Age Security, Claim System and Procedures, BPJS Ketenagakerjaan, Jamsostek Mobile (JMO) Application